TUBERKULOSIS RENAL - Irene R. T. Damanik (Universitas Methodist Indonesia, 2017)
Renal TB accounts for 14–41% of all cases of pulmonary TBC in developed countries, that usually occurs 5–15 years after primary pulmonary infection with complication in 3–4%. Non-specific constitutional and insidious onset and symptoms lead to delayed diagnosis also rapid progression to a non-functioning kidney. Imaging is important to making of a timely diagnosis and in the planning of treatment, complications such as renal failure. Genitourinary TB imaging are outlined, from the pathognomonic lobar calcification on plain film, such as papillary necrosis on intravenous urography (IVP),loss of calyceal sharpness, uneven caliectasis and urothelial thickening, in the absence of renal pelvic dilatation, hitherto unreported ‘lobar caseation’ on ultrasonography (USG).Coalesced cortical granulomas containing either caseous or calcified material are readily identified at CT scan, especially related to the use of the newer modalities such as magnetic resonance imaging (MRI).Preoperative diagnosis is recommended if the grade of suspicion is high in order to avoid the need for surgery.